Plectranthus sahyadricus (Lamiaceae): a new species from Western Ghats, India - Smitha, Kokkaraniyil; Sunojkumar, Purayidathkandy (Phytotaxa, 2018)
A new species, Plectranthus sahyadricus is described from Munnar, southern Western Ghats, India. The species shows similarity with Plectranthus beddomei, in its stem and leaf characters but differs mainly by presence of a ring of hairs at young nodes, floral characters like cyme length, number of flowers per cyme, structure of the fruiting calyx tube, anterior corolla lip not fully opened and form an inverted dome over mouth, presence of hairs inside corolla tube and size of the disc. Detailed description, IUCN red list category and other relevant notes are provided.